Labour supply of married females in Estonia - Boriss Siliverstovs; Dmitri Koulikov (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
In this paper we estimate the labor supply function for married females in Estonia. Particularly, we are interested in determining the elasticities of the weekly supply ofhours with respect to hourly wage rates and with respect to nonlabor income. We adopt the two-step estimation procedure. In the first step, we obtain parameter estimates of the self-selection corrected wage equation. At this stage, we document the absence of the sample selection bias in our data as well as the significant negative effect of nonproficiency in the Estonian language on the hourly wage rate. In the second step, the labor supply function is estimated using the Tobit model, where the predictions from the wage equation substitute for the market wage rates for all individuals. We find that the wage elasticity of hours supplied per week is positive (0.53), while at the same time the nonlabor income effect is insignificant.
Keywords: P36; J31; J22; 330; Female Labor Supply; Transition Economics; Estonian Labor Market; Frauenerwerbstätigkeit; Arbeitsangebot; Ehe; Schätzung; Übergangswirtschaft; Estland